Carbon footprint of rice production under biochar amendment – a case study in a Chinese rice cropping system - Liu, Qi; Liu, Benjuan; Ambus, Per; Zhang, Yanhui; Hansen, Veronika; Lin, Zhibin; Shen, Dachun; Liu, Gang; Bei, Qicheng; Zhu, Jianguo; Wang, Xiaojie; Ma, Jing; et al. (Global change biology. Bioenergy, 2016)
As a controversial strategy to mitigate global warming, biochar application into soil highlights the need for life cycle assessment before large‐scale practice. This study focused on the effect of biochar on carbon footprint of rice production. A field experiment was performed with three treatments: no residue amendment (Control), 6 t ha−1 yr−1 corn straw (CS) amendment, and 2.4 t ha−1 yr−1 corn straw‐derived biochar amendment (CBC). Carbon footprint was calculated by considering carbon source processes (pyrolysis energy cost, fertilizer and pesticide input, farmwork, and soil greenhouse gas emissions) and carbon sink processes (soil carbon increment and energy offset from pyrolytic gas). On average over three consecutive rice‐growing cycles from year 2011 to 2013, the CS treatment had a much higher carbon intensity of rice (0.68 kg CO2‐C equivalent (CO2‐Ce) kg−1 grain) than that of Control (0.24 kg CO2‐Ce kg−1 grain), resulting from large soil CH4 emissions. Biochar amendment significantly increased soil carbon pool and showed no significant effect on soil total N2O and CH4 emissions relative to Control; however, due to a variation in net electric energy input of biochar production based on different pyrolysis settings, carbon intensity of rice under CBC treatment ranged from 0.04 to 0.44 kg CO2‐Ce kg−1 grain. The results indicated that biochar strategy had the potential to significantly reduce the carbon footprint of crop production, but the energy‐efficient pyrolysis technique does matter.